Student teachers’ reflections of advantages, disadvantages, and learning related to lecturers' different pedagogical methods - Arne Sørensen; Pål Lagestad (Physical Education of Students)
Background and Study Aim. Improving the quality of teaching in higher education is essential. Equally important is obtaining a detailed understanding of students' reflections on their educational experiences. The purpose of this study was to evaluate students’ reflections related to their learning and the advantages and disadvantages of different pedagogical methods.